COPD management in primary care: is an educational plan for GPs useful? - Bertella, Enrica; Zadra, Alessandro; Vitacca, Michele (Multidisciplinary Respiratory Medicine, 2013)
Background: GPs currently deal with COPD. The aim of this study was to review COPD management, data collection in medical records, and adherence to GOLD guidelines of 12 GPs from rural areas of Northern Italy and to assess changes after an educational program (EP). Methods: From 2004 to 2008 medical records of patients, defined as COPD by GPs, were analyzed. Data collection in terms of tests prescription, Forced Expiratory Volume at first second (FEV1), smoking habits and actual drug treatment were reviewed at baseline and 1 year after EP. Results: 437 patients were defined as COPD. GPs prescribed more chest X-rays than spirometry (99% vs. 74%, p